Sub-threshold sense amplifier compensation using auto-zeroing circuitry - Beshay, P.; Calhoun, B. H.; Ryan, J. F. (2012 IEEE Subthreshold Microelectronics Conference, 2012)
Voltage offset in SRAM sense amplifiers due to variability causes increased power consumption and degraded performance. The effect is more dominant in the sub-threshold region. In this paper, we propose a circuit that reduces the sense amp offset using an auto-zeroing scheme with automatic temperature, voltage, and aging tracking.